Recepcja Żywotów świętych ks. Piotra Skargi Tj w twórczości św. Dymitra z Rostowa - Jankowska, Ludmiła (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
As a conclusion of an in-depth analysis of the current state of research on the topic, the article presents a multitude of literary sources, mainly in manuscript format. These include, above all, the hand-written notes of Saint Dmitry from Rostow on the pages of three editions of Żywoty Świętych (Lives of the Saints) — up to now the most popular encyclopaedia of Christian sanctity. It is claimed that this most prominent Ukrainian-Russian religious writer many a time compared various sources, including Żywoty Świętych by Skarga. This allowed him to obtain more specified information regarding particular saints or even to make corrections in Prolog (The Prologue) and in Mineje (The Menaion). What is more, Saint Dmitry has not only learned to compile several sources from Piotr Skarga, but he also manager to achieve stylistic unity.